2015
DOI: 10.1111/mec.13388
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional variation associated with cactus host plant adaptation in Drosophila mettleri populations

Abstract: Although the importance of host plant chemistry in plant-insect interactions is widely accepted, the genetic basis of adaptation to host plants is not well understood. Here, we investigate transcriptional changes associated with a host plant shift in Drosophila mettleri. While D. mettleri is distributed mainly throughout the Sonoran Desert where it specializes on columnar cacti (Carnegiea gigantea and Pachycereus pringleii), a population on Santa Catalina Island has shifted to chemically divergent coastal pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 51 publications
(114 reference statements)
4
78
1
1
Order By: Relevance
“…Pervasive host-insensitivity in the expression of detoxification genes appears to be the rule across plant-eating insects [18, 45]. However, we did find that ABC transporters were more differentially expressed across hosts than expected by chance.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Pervasive host-insensitivity in the expression of detoxification genes appears to be the rule across plant-eating insects [18, 45]. However, we did find that ABC transporters were more differentially expressed across hosts than expected by chance.…”
Section: Discussioncontrasting
confidence: 58%
“…Most of the significant host-induced changes in gene expression do not appear to be related to detoxification. For example, researchers have found consistent host-dependent expression of many genes involved in primary metabolism [8, 18]. Furthermore, some studies have recovered evidence of a trade-off between expression of genes for detoxification and primary metabolism [7, 18]; for some plant-eating insects, increased investment in the expression of detoxification genes may come at the cost of reduced investment in growth and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in gene expression paralleled phenotypic differences between populations: inter-population differences in expression of some genes involved in metabolism and larval development also depended on the host species on which flies were reared (Etges et al 2015). A similar study found a diverse suite of genes – enriched for functions in detoxification, metabolism, and sensory perception – that exhibited host-dependent expression level differences between populations of D. mettleri specializing on different host cacti (Hoang et al 2015). While these transcriptomic studies revealed insights into the likely physiological basis of local adaptation in cactophilic Drosophila , population genomic scans coupled with genome-wide measurements of allele frequency change during exposure to local and non-local hosts could definitively identify the targets of selection and genomic architecture of local adaptation.…”
Section: Local Adaptationmentioning
confidence: 83%
“…) and Drosophila mettleri (Hoang et al . ). These studies mainly focused on polyphagous insects (or generalists) feeding on different hosts and detected the expression patterns of differentially expressed genes.…”
Section: Introductionmentioning
confidence: 97%